Subsidies with export share requirements in China - Defever, Fabrice; Riaño, Alejandro (Elsevier, 2017)
A subsidy is subject to an export share requirement (ESR) when firms must export more than a certain share of their output to receive it. Such incentives are frequently found in free trade zones, export processing regimes and measures targeted at foreign investors, both in China and other developing countries. In this paper we provide the first quantitative assessment of the effect that using subsidies with ESR has on exports, the intensity of competition and welfare, both in the enacting country and its trading partners, using a two-country model of trade with heterogeneous firms. We find that the subsidy with ESR boosts exports more than an equivalent unconditional subsidy available to all exporters. Crucially, the subsidy with ESR provides greater protection to low-profitability firms, while the unconditional subsidy does the opposite. The combination of export promotion and lower intensity of domestic competition generated by the subsidy with ESR can be described as "protectionism through exporting." The imposition of an ESR, however, greatly exacerbates the welfare loss associated with subsidizing exporters.